Full-scale simulation of a 372 kW/372 kWh whole-cluster immersion cooling lithium-ion battery cluster and battery thermal management system design - Xi Cao; Qianlei Shi; Qian Liu; Mingyi Liu; Chuanliang Xiong; Bailian Peng; Chuanzhao Cao; Xianfa Wang; Yizhao Chen; Qian Cheng; Wei Liu; Chengjun Wen; et al. (Case Studies in Thermal Engineering)
The battery thermal management system (BTMS) is a necessary consideration to ensure the efficiency, safety, and reliability of battery energy storage systems (BESS). Immersion cooling, with its high heat transfer efficiency and uniform heat distribution, is emerging as the trend in BTMS. This study investigated a 372 kW/372 kWh BESS utilizing the immersion cooling technique, where the entire cluster of batteries is immersed in a coolant. The large-full-scale simulation model is established to analyze the flow and temperature performance. 3 types of immersion coolant are compared, which are 10# transformer oil (DF1), silicone oil-5cSt (DF2), and natural ester RAPO (DF3). The conclusion shows that DF2 is the optimal immersion liquid for the battery cluster, for the lowest average temperatures, which are 26.30 °C and 36.91 °C during 0.5 P and 1 P discharge, respectively. Based on the temperature uniformity index (UTave,s), DF1 represents the best temperature uniformity, with the value of 0.034 and 0.047 during 0.5P and 1P discharge, respectively. Because of the high viscosity of DF3, it achieves the highest system pressure drop and the worst temperature uniformity, which shows that DF3 are not suitable to be selected as immersion coolant.